Evaluating community care : services for people with learning difficulties - Wright, Ken.; Haycox, Alan.; Leedham, Ian. (Buckingham : Open University Press, 1994)
The evaluation framework. The policy background. Definition and methodology. Specific research dimensions and their measurement. Evidence and issues. Cost measurement in theory. Cost measurement in pratice.
Keywords: Great Britain; Mentally handicapped; Mental health services; Mentally handicapped -- Services for -- Great Britain -- Evaluation; Learning disabled -- Services for -- Great Britain -- Evaluation; Mental health services -- Great Britain -- Evaluation